(3dH GddHGH aj JMQjQ GdCfSGHs - (3YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj, CHh SYO,J (B562 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CMSf cd TF s
(3BNQgG (B:s
(3jfJgi HBNQ MQa GdNGA s
(3GdehLhO efg GdLRA GdChds
(3GfXQ Qbe (B769 (3JGQjNs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B4s
Keywords: (3GdJGQjNs